End-of-pipe and cleaner production technologies. Do policy instruments and organizational capabilities matter? Evidence from Spanish firms. (15th March 2022) - Garcia-Quevedo, J.; Martinez-Ros, E.; Tchorzewska, K.B.
Abstract: This paper focuses on the drivers of green technology adoption. We distinguish between end-of-pipe and cleaner production technologies aimed at either pollution mitigation or energy efficiency, respectively. We provide empirical evidence of the relations between existing policy instruments, organizational capabilities of firms and the adoption of different types of green technologies. We use a unique firm level panel dataset of 2562 Spanish manufacturing firms from 2008 to 2014 to carry out the empirical analysis. Our results show, first, that policy instruments drive adoption of green innovation more than organizational capabilities. Second, environmental taxation seems to be ineffective at stimulating the adoption of eco-innovation. Third, both investment subsidies and tax credits do imply higher levels of investments in green technologies. Tax incentives seem to mostly foster cleaner production technologies, while subsidies are used to finance all types of eco-innovations. Fourth, human resources as green employees are positively related with environmental investments. Finally, dynamic capabilities as the introduction of environmental management systems are correlated particularly with cleaner production investments oriented to reduce energy consumption. Highlights: Policy instruments drive eco-innovation more than organizational capabilities. Environmental taxation is not successful at encouraging green investments. Green employees induce environmental investments. Management eco-systems are correlated with cleaner production investments (energy).